Structure and function of eTudor domain containing TDRD proteins. (4th March 2019) - Gan, Bing; Chen, Sizhuo; Liu, Huan; Min, Jinrong; Liu, Ke
Abstract: Tudor domain-containing (TDRD) proteins, as a family of evolutionarily conserved proteins, have been studied extensively in recent years in terms of their biological and biochemical functions. A major function of the TDRD proteins is to recognize the N-terminal arginine-rich motifs of the P-element-induced wimpy testis (PIWI) proteins via their conserved extended Tudor (eTudor or eTud) domains, which is essential in piRNA biogenesis and germ cell development. In this review, we summarize recent progress in the study of the TDRD proteins, and discuss the molecular mechanisms for the different binding selectivity of these eTudor domains to PIWI proteins based on the available binding and structural data. Understanding the binding differences of these TDRDs to PIWI proteins will help us better understand their functional differences and aid us in developing the target-specific therapeutics, because overexpression or mutations of the human TDRD proteins have been demonstrated to associate with various diseases.